Contribution of Asian mouse subspecies Mus musculus molossinus to genomic constitution of strain C57BL/6J, as defined by BAC-end sequence–SNP analysis - Abe, Kuniya; Noguchi, Hideki; Tagawa, Keiko; Yuzuriha, Misako; Toyoda, Atsushi; Kojima, Toshio; Ezawa, Kiyoshi; Saitou, Naruya; Hattori, Masahira; Sakaki, Yoshiyuki; Moriwaki, Kazuo; Shiroishi, Toshihiko

(untitled) (Genome Research, 2004)
MSM/Ms is an inbred strain derived from the Japanese wild mouse, Mus musculus molossinus. It is believed that subspecies molossinus has contributed substantially to the genome constitution of common laboratory strains of mice, although the majority of their genome is derived from the west European M. m. domesticus. Information on the molossinus genome is thus essential not only for genetic studies involving molossinus but also for characterization of common laboratory strains. Here, we report the construction of an arrayed bacterial artificial chromosome (BAC) library from male MSM/Ms genomic DNA, covering ∼1× genome equivalent. Both ends of 176,256 BAC clone inserts were sequenced, and 62,988 BAC-end sequence (BES) pairs were mapped onto the C57BL/6J genome (NCBI mouse Build 30), covering 2,228,164 kbp or 89% of the total genome. Taking advantage of the BES map data, we established a computer-based clone screening system. Comparison of the MSM/Ms and C57BL/6J sequences revealed 489,200 candidate single nucleotide polymorphisms (SNPs) in 51,137,941 bp sequenced. The overall nucleotide substitution rate was as high as 0.0096. The distribution of SNPs along the C57BL/6J genome was not uniform: The majority of the genome showed a high SNP rate, and only 5.2% of the genome showed an extremely low SNP rate (percentage identity = 0.9997); these sequences are likely derived from the molossinus genome.